2023
DOI: 10.30574/wjarr.2023.17.2.0190
|View full text |Cite
|
Sign up to set email alerts
|

Overview of male breast cancer

Abstract: Breast cancer (BC) is an epithelial neoplastic disease that usually begins in the ducts or lobules of the breast with the potential to spread to other parts of the body. BC is primarily a disease that affects females but can also occur in men due to the presence of (limited) male breast tissue. Nevertheless, male breast cancer (MBC) should not be seen as just the occurrence of female breast cancer (FBC) in males. Males share common risk factors with postmenopausal women including age, family history, breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 69 publications
(95 reference statements)
0
0
0
Order By: Relevance
“… 29 It is also reported that hormone receptor expression is more common in MBC when compared with FBC. 92 Hence, inhibition of these receptors could be usually predicted for the treatment and management of MBC, which will be discussed under the treatment modalities in the further sections.…”
Section: Ductal Carcinoma In Situ (Dcis)mentioning
confidence: 99%
See 1 more Smart Citation
“… 29 It is also reported that hormone receptor expression is more common in MBC when compared with FBC. 92 Hence, inhibition of these receptors could be usually predicted for the treatment and management of MBC, which will be discussed under the treatment modalities in the further sections.…”
Section: Ductal Carcinoma In Situ (Dcis)mentioning
confidence: 99%
“…The same chemotherapeutic agents and regimens that are being used to treat FBC could be used for metastatic MBC treatment. 92 , 113 , 117 , 148 …”
Section: Ductal Carcinoma In Situ (Dcis)mentioning
confidence: 99%